Analysis of social representations of languages ​​and bi-plurilingual education among teachers and future teachers in French-speaking sub-Saharan Africa - (:unkn) unknown (My University, 2022)
In this article, we present a study that began in April 2020 and will continue throughout 2021 with teachers and students in French-speaking sub-Saharan Africa. The study consists in an analysis of their social representations of the French language and of African languages as well as an analysis of their social representations of bi-plurilingual education. To carry out this study, we implement the «combined method of analysis of social representations» (Maurer, 2013).
Keywords: African Research